Digital culture and society - Orton-Johnson, Kate (London SAGE Publications Ltd., 2024)
Kate Orton-Johnson explores the digital in relation to the 'social', tying content to concepts such as interaction, power, consumption, gender
and the self. Exploring questions of methodology throughout, case studies illustrate theory-in-practice and integrate questions of
methodology and digital tools
Includes bibliographical references and index.
Keywords: Digital media -- Social aspects; Information society; Media Studies